A REVIEW OF CLINICAL PROFILE AND GLYCEMIC CONTROL OF PATIENTS WITH YOUNG-ONSET TYPE 2 DIABETES MELLITUS ON INTENSIVE INSULIN THERAPY - Lingeswary, Krishnan; Tee, Ai Xuan; Ibrahim, Wan; Atiqah, Sheril; Lee, Teng Lin; Nagaratnam; Shamharini (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Young-onset type 2 diabetes mellitus (T2D) is a more aggressive subgroup of T2DM with rapid disease progression and rate of complications. Many patients progress to intensive insulin therapy early in the disease process due to decompensation and poor glycaemic control. METHODOLOGY We aimed to review the demographic profile, glycaemic control, and prevalence of complications in patients with young T2DM on intensive insulin therapy at the Endocrine Institute of Hospital Putrajaya. A retrospective audit was conducted using electronic medical records. Patients with T2DM between the age of 18-40 years on basal-bolus insulin therapy attending the outpatient diabetes clinic between January 2022 – March 2024 were included. Data about the demographic profile, insulin therapy, glycaemic control and complications were collected. A descriptive analysis using SPSS version 25.0 was performed. RESULTS The analysis involved a total of 72 cases, with a mean age of 33.7 years. Females comprised two-thirds (68.1%), with Malays being the majority (81.9%). The mean weight was 85.3 kg and the mean BMI was 32.1 kg/m2 . The mean duration of diabetes was 10.1 years. Among them, 62.5% have comorbidities such as hypertension and dyslipidaemia, and 48.6% are obese. The average duration of insulin therapy was 5.9 years. The mean HbA1c was 10.3% before insulin therapy and 9.5% on current intensive insulin therapy. Microvascular complications were prevalent (73.6%), with nephropathy being the most common (59.6%), followed by retinopathy and neuropathy. Approximately 5% of patients had macrovascular disease. More than two-thirds (70.8%) were on statin and half (56.9%) were on antiproteinuria therapy. CONCLUSION Most patients with young-onset T2DM have poor glycaemic control despite being on intensive insulin therapy. Most patients fit the phenotype of obesity with metabolic syndrome suggesting possible insulin resistance, as opposed to depletion, as the key factor driving disease progression. Treatment strategies employed should focus on intensive lifestyle intervention and pharmacotherapy targeting weight reduction and insulin resistance as opposed to excessive insulin in this subgroup.